2007
DOI: 10.1007/s10508-007-9291-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Sex Hormones (Maternal and Amniotic Fluid) and Gender-related Play Behavior in 13-month-old Infants

Abstract: Testosterone, estradiol, and progesterone levels were measured in the second trimester of pregnancy in maternal serum and amniotic fluid, and related to direct observations of gender-related play behavior in 63 male and 63 female offspring at age 13 months. During a structured play session, sex differences in toy preference were found: boys played more with masculine toys than girls (d = .53) and girls played more with feminine toys than boys (d = .35). Normal within-sex variation in prenatal testosterone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 55 publications
1
42
0
2
Order By: Relevance
“…Thus, they provide convergent evidence, with the data from studies of CAH and of maternal testosterone, of influences of prenatal testosterone exposure on subsequent sex-typical behavior in childhood. Although two other similar studies found insignificant correlations between testosterone in amniotic fluid and childhood sex-typed behavior [87;135], these negative results could have resulted from small sample sizes and from the use of relatively insensitive behavioral measures.…”
Section: Hormones and Sexual Differentiation Of Childhood Behaviormentioning
confidence: 97%
“…Thus, they provide convergent evidence, with the data from studies of CAH and of maternal testosterone, of influences of prenatal testosterone exposure on subsequent sex-typical behavior in childhood. Although two other similar studies found insignificant correlations between testosterone in amniotic fluid and childhood sex-typed behavior [87;135], these negative results could have resulted from small sample sizes and from the use of relatively insensitive behavioral measures.…”
Section: Hormones and Sexual Differentiation Of Childhood Behaviormentioning
confidence: 97%
“…Although two studies reported no relationship between aT and sex -typical play (Knickmeyer et al, 2005 ;van de Beek, van Goozen, Buitelaar, & Cohen -Kettenis, 2009 ), these studies may have lacked suffi cient experimental power to detect effects. The fi rst study assessed childhood behavior by maternal report in 22 girls and 31 boys, and the second by observed toy choice in 63 girls and 63 boys.…”
Section: Biological E Xplanationsmentioning
confidence: 99%
“…Umbilical cord blood androgens are likely to reflect the fetal androgen environment during late gestation. However, a major limitation of the use of cord blood is that it is possible that androgen influences on development may occur earlier in gestation (34). …”
Section: Biological Interpretation Of Cord Blood Hormonesmentioning
confidence: 99%